Religious moderation in Madrasah Aliyah Wahid Hasyim Balung – Jember - Priyono, Dwi Juli (Institute of Computer Science (IOCS), 2024)
This research aims to determine the concept of planning and implementing religious moderation in PAI learning at Madrasah Aliyah Wahid Hasyim Balung. This research involved 13 participants, namely 3 PAI teachers and 10 students who were involved in material-based PAI learning about religious moderation. The results of this research discuss: 1. Design of curriculum planning based on religious moderation in PAI textbooks, 2. Design of curriculum implementation based on religious moderation in PAI textbooks, and 3. Results of implementation of a curriculum based on religious moderation in PAI textbooks at MA Wahid Hasyim Balung – Jember. The implication of this research is that students can understand and apply their understanding of Tolerance (Tasamu?), Equality (Musawah), Moderation (Tawasuth), Mutual Brotherhood (Ukhuwwah) well in Madrasah where this material is contained in PAI subjects. namely Aqidah Akhlak, SKI, and Al-Qur'an Hadits. Apart from that, evidence of students' understanding regarding religious moderation is the creation of a feeling and attitude of mutual respect and respect in learning activities, in social interactions, and in carrying out worship activities at MA Wahid Hasyim Balung - Jember.